Respuesta :
To simplify this expression, we can combine like terms.
= 11x - 7 - 3x + 4
= (11x - 3x) + (-7 + 4)
= 8x - 3
Best of Luck!
Answer:
8x - 3
Step-by-step explanation:
Simplify 11 x - 7 - 3 x + 4........................................................................(the question)
in order to simplify 11 x - 7 - 3 x + 4
we first of all rearrange the expression in order words collecting the like terms.
we have,
=11x-3x-7+4
=8x -7+4
=8x - 3
therefore the simplified form of the expression 11 x - 7 - 3 x + 4 is
8x - 3